Bioaccessibility of phenolic compounds from sesame seeds (Sesamum indicum L.) during in vitro gastrointestinal digestion and colonic fermentation. Issue 7 (26th April 2022) - Luo, Jiani; Li, Minhao; Wu, Hanjing; Liu, Ziyao; Barrow, Colin; Dunshea, Frank; Suleria, Hafiz A. R.
Abstract: Sesame ( Sesamum indicum L.) is an oilseed crop and rich in various bioactive compounds including phenolics, phytosterols, and vitamins. In this study, phenolic compounds were extracted from three varieties of sesame seeds (black, brown, and white) to determine the antioxidant activities and bioaccessibility of selected phenolic compounds during in vitro digestion and colonic fermentation. The SCFAs production was also estimated. Black sesame seeds performed the highest total phenolic content (TPC) (2.69 mg GAE/g) and antioxidant capacities during gastrointestinal digestion. During colonic fermentation, black and brown sesame seeds exhibited relatively higher TPC (4.13 mg GAE/g) and antioxidant activities (DPPH: 8.6 mg TE/g; FRAP: 4.1 mg TE/g). Kaempferol was the lowest bioaccessible phenolic compound presented in all three sesame seeds, which relied more on the action of gut microbiota. White sesame seeds displayed higher production of individual and total SCFAs followed by black sesame seeds, which could be beneficial to gut health. Novelty impact statement: Black and brown sesame seeds showed relatively higher content of phenolic compounds and remarkable antioxidant potential during in vitro gastrointestinal digestion and colonic fermentation. The bioaccessibility of phenolic compounds present in brown and white sesame seeds was relatively higher than in black sesame seeds. Most of the detected phenolic compounds in selected sesame seeds were fully bioaccessible after 24 h of colonic fermentation, except kaempferol. White and black sesame seeds showed higher production of SCFAs, which would be more beneficial to gut health.